G476(P) Trimethylaminuria: A case report. (7th April 2014) - Sabir, N; Padmakumar, B
Abstract : Background: Trimethylaminura; also known as Fish-Odour Syndrome; is an inherited disorder characterised by a body odour likened to that of rotting fish. This metabolic condition caused by deficient N-oxidation and increased excretion of trimethylamine, is attributed to mutations affecting the flavin-containing monooxygenase–3 (FMO3) gene. Affected individuals have consequent offensive smelling breath, sweat, urine and other bodily secretions. Case: A 9-year-old boy was admitted to general paediatric clinic. The presenting complaint was a two year history of distinctive fish-like smell from his hands, feet, breath and sometimes urine. He was full term normal vaginal delivery with no developmental concerns. There were no other medical problems. He was the first child to consanguineous parents. To note, his 14-year-old cousin was thought to have a similar problem. Results: When tested, the patient's urine had an increased ratio of trimethylamine to trimethyamine N-oxide. He was then referred to a geneticist who arranged for FMO3 gene analysis, which was homozygous in exon 5, confirming the diagnosis of primary trimethylaminuria. The patient was advised against consuming foods containing choline such as eggs and fish. This conservative approach improved the symptoms significantly. Conclusion: Trimethylaminura is a rare autosomal recessive inherited disorder, characterised by a distinctive fish odour in all bodily secretions. Until recently, it has been diagnosed clinically, however, with genetic testing definitive diagnoses can now be made, and simple measures can improve symptoms and consequent quality of life.